From Pathophysiology to Treatment: The Role of Ferroptosis in PCOS - Jie An; Qin Zhou; Xiaojing Guo; Congya Xu; XiaoFang Jia; Zhenzhen Cao; Qibin Lu (Frontiers in Bioscience-Landmark)
Polycystic ovary syndrome (PCOS) is a prevalent gynecological endocrine and metabolic disorder in women, with an incidence rate of 10–13%. The etiology of PCOS is multifaceted, involving genetic predisposition, environmental influences, lifestyle factors, and endocrine metabolic dysregulation. Iron, a critical mineral, not only plays a role in regulating female physiological functions and the progression of PCOS but also requires careful management to avoid deficiency. However, excess iron can trigger ferroptosis, a form of nonapoptotic cell death characterized by the accumulation of lipid peroxides. While numerous studies have explored ferroptosis in patients with PCOS and animal models, the precise mechanisms and therapeutic implications remain inadequately understood. This review seeks to elucidate the pathophysiology of PCOS and the contributory factors of ferroptosis. Additionally, we examine the diverse manifestations of ferroptosis in PCOS and evaluate its role. Furthermore, we introduce ferroptosis-related traditional Chinese medicines that may enhance the understanding of PCOS pathogenesis and aid in the development of targeted therapies for ferroptosis in PCOS.